Mental Disorders Following War in the Balkans – A Study in Five Countries - Priebe, Stefan (Array, 2010)
Context War experience may impact on mental health. However, in a Western context no community-based study has assessed mental disorders several years after war using consistent random sampling of war affected people across several countries. Objectives 1) To assess current prevalence rates of mental disorders in an adult population who were directly exposed to war in the Balkans and still live in the area of conflict, and 2) to identify factors associated with the occurrence of different types of mental disorders. Design, Setting, and Participants War affected community samples in Bosnia- Herzegovina, Croatia, Kosovo, FYR Macedonia, and Serbia were recruited through a random walk technique. Main Outcome Measure Prevalence rates of mood, anxiety and substance use disorders were assessed using the MINI International Neuropsychiatric Interview. Results Between 637 and 727 interviewees were assessed in each country with a total sample of 3313. The prevalence rates of anxiety disorders ranged from 15.6% to 41.8%, of mood disorders from 12.1% to 47.6%, and of substance use disorders from 0.6% to 9.0%. In multivariable analyses across countries, older age, female gender, more potentially traumatic experiences during and after the war, and unemployment were associated with higher rates of mood and anxiety disorders. Additionally, mood disorders were correlated with lower education and more potentially traumatic experiences before the war. Male gender and not living with a partner were the only 5 factors associated with higher rates of substance use disorders. 81 s. Most of these associations did not significantly differ between countries. Conclusions Several years after the end of the war, the prevalence rates of mental disorders in war affected people vary across countries, but are generally high. War experiences appear linked to anxiety and mood disorders, but not substance use disorders. Long-term policies to meet the mental health needs of war affected populations are required.